Emamectin·chlorfenapyr-induced fatal leukoencephalomyelopathy with delayed hyperthermia: insecticide endanger public safety - Li, Xun; Yang, Yun; Zhang, Yajing; Zhang, Xuebin; Zhao, Na; Yue, Wei (Frontiers in Neurology, 2024)
BackgroundEmamectin·chlorfenapyr is a compound comprising chlorfenapyr and emamectin benzoate that is widely used in agriculture. Chlorfenapyr toxicity has been verified in animals; however, its true mechanism and progression in humans remain to be elucidated. Cases of emamectin·chlorfenapyr poisoning are seldom.Case presentationWe present a case of a 65-year-old female who attempted suicide by consuming 30 g of 9.5% chlorfenapyr and 0.5% emamectin benzoate 14 days before admission to our hospital. Laboratory tests revealed extremely high creatinine kinase levels upon admission. Magnetic resonance imaging revealed diffuse and symmetric T2 hyperintensities in the entire white matter tract of the brain and spinal cord, and cytological smears of the cerebrospinal fluid showed abnormal lymphocyte aggregation. The patient died 19.5 h after admission owing to cardiopulmonary arrest and hyperthermia.ConclusionFurther research is needed on how to perform flow cytometry in patients with emamectin·chlorfenapyr intoxication, and to elucidate the immunological mechanism underlying the inflammatory response caused by emamectin·chlorfenapyr and provide new insights into antidote development.